Lowering CO2 emissions in the Swiss transport sector - Philippe Thalmann; Marc Vielle (Swiss Journal of Economics and Statistics, 2019)
In Switzerland, transportation represents 41% of CO2 emissions from energy combustion (2016), a much higher share than in the European Union (EU) (28%) or even the USA (34%). While total Swiss CO2 emissions decreased by 10% between 1990 and 2016, CO2 emissions from transport increased by 4.5% over the same period (all data from UNFCCC database). Our projections (Vielle and Thalmann, Updated emissions scenarios without measures, 1990-2025, Tech. rep., 2017) show that the contribution of the transport sector would remain constant in a scenario taking into account climate and energy policy measures already implemented or adopted in 2016. In the EU, several initiatives have already been introduced to limit the use of petroleum products in transportation. This paper presents deep decarbonization pathways for Switzerland that demand a strong contribution from the transport sector. We find that a preferential treatment of transportation fuels raises the welfare cost of decarbonization by about 18% relative to a uniform tax on all fossil fuels. This is of similar magnitude as the preferential treatment of large CO2 emitters through an emissions trading system. We also find that the preferential treatment leads to a share of fossil fuels in total energy for road transportation in 2050 which is approximately twice as high as in the uniform treatment.
Keywords: C63; Q41; Q54; 330; Climate policy; Transport decarbonization; Computable general equilibrium model; Switzerland